Consideration for the scale‐up manufacture of nanotherapeutics—A critical step for technology transfer. Issue 5 (12th July 2021) - Liu, Xiangsheng; Meng, Huan
Abstract: While nano‐enabled biotechnology is offering great promise, in certain areas providing fundamental paradigm shift for disease management, we are rapidly moving into a new era of nanotechnology developmental stage, in which chemistry, manufacturing, and controls of nanotherapeutics ( nano ‐CMC) become a critical step for translational nanomedicine. This is not a trivial task, in fact, nano ‐CMC requires a long list of considerations. Minimally, it includes raw materials, scale‐up synthesis routes, batch sizes, stability check, analytical methods, and documentation. The growing items on the list could collectively ensure the reproducible production of nanotherapeutics that are safe and efficacious and meet new drug application (NDA) specifications. This article begins from the lesson learned from liposome, such as Doxil ® and other FDA‐approved liposomes, then continues to provide a literature summary on the scale‐up synthesis of nanoparticles that were designed for therapeutic or diagnostic purposes. We outlined the key challenges during the scale‐up activities, followed by the case studies to illustrate the impact of emerging strategies that may improve the reproducible synthesis of large‐batch nanoparticles. The availability of quality‐controlled large‐batch size opens the possibility to conduct robust preclinical studies and clinical trials. This includes the recent advances of using microfluidics system, implementation of multiparameters iterative CMC optimization, and use of computer software, allowing the successful preparation of different organic and inorganic nanoparticles at desired batch sizes. The authors also share personal insights with respect to how nano‐ CMC research would facilitate "personalized and just‐in‐time" nanomedicine. Abstract : Chemistry, manufacturing, and controls of nanotherapeutics ( nano ‐CMC) is a critical step for translational nanomedicine. Establishment of reproducible, scalable, transferrable, and controllable nanomanufacture process is a major barrier that needs to be overcome in terms of moving various nanotherapeutics from bench to bed.